2018
DOI: 10.1038/s41433-018-0018-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of combined pars plana vitrectomy and trans-scleral 4-point suture fixation of a foldable intraocular lens

Abstract: Trans-scleral 4-point suture fixation of a foldable Akreos AO60 IOL can be performed safely along with concurrent PPV across varying surgical indications resulting in a substantial improvement in visual acuity with minimal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
(42 reference statements)
1
19
0
3
Order By: Relevance
“…[1,6,[14][15][16][17][18][19][20][21] Retrospective studies have shown good results of scleral fixation using the Akreos AO60 lens and Gore-Tex suture. [5,7,[9][10][11][12][13] To our knowledge and based on a computerized search of the Medline database, this is the first prospective study of Akreos A060 scleral fixation with Gore-Tex suture and it confirms that the technique is safe and promotes good visual results.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…[1,6,[14][15][16][17][18][19][20][21] Retrospective studies have shown good results of scleral fixation using the Akreos AO60 lens and Gore-Tex suture. [5,7,[9][10][11][12][13] To our knowledge and based on a computerized search of the Medline database, this is the first prospective study of Akreos A060 scleral fixation with Gore-Tex suture and it confirms that the technique is safe and promotes good visual results.…”
Section: Discussionmentioning
confidence: 68%
“…This group used a similar technique to that employed herein although, in addition to using prolene, they created scleral flaps, which can be a technique to reduce the risk of conjunctival erosion by the suture. Similarly, Goel et al (2018) [11] stated that the use of scleral flaps and the rotation of the suture knots decrease the risk of suture erosion. In their 2015 [7] and 2018 [9] publications, Khan et al did not observe any suture-related complications, including rupture, erosion, IOL dislocation or inclination, endophthalmitis, or persistent postoperative inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies evaluating scleral fixation have shown a mild myopic shift from targeted postoperative refraction. 17 , 20 , 23 , 24 Ohr et al specifically studied scleral fixation of Akreos lenses and has shown reliable postoperative refractive outcomes with a myopic shift. 20 Our evaluation corroborated the results of previous studies of Gore-Tex sutured lenses with a significant majority (75%) of our patients having a myopic shift in the difference between actual and targeted SE.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, if we fixed the sutures at the both symmetrical points of the middle haptics, pulled the haptics just touching the ciliary sulcus, and completely removed the residual capsule and anterior vitreous body, it is easier to maintain the IOL balance and centralization (Figure 4). Besides, a little study uses three or four haptics, but there are many disadvantages such as many incisions, increased damages, complex operative procedures, easy deformation of IOLs, eccentricity and so on [46].…”
Section: Discussionmentioning
confidence: 99%